Digitalization Training In The Promotion Of Keciput Tourism Village, Bangka Belitung Province - Indawan Saputri, Benedikta Jenika; Setyaningsih, Mei Putri; Fauziah, Hana; Azizah, siti Nur (EMPOWERING HUMANITY, 2023)
The use of social media in the Keciput tourist village to promote the tourist village has been carried out with an Instagram account. However, social media contents are less exciting and informative, so it is necessary to develop the content. Implementing community service in the Keciput tourist village focuses on training activities for making Instagram social media by filling in exciting and informative content. On the other hand, this service activity also holds training related to tourism digitization. The outcome of this community service is the existence of a unique Instagram for tourism content with interesting, informative content in the Keciput tourist village. The conclusion obtained from this community service is that there is community enthusiasm from the Keciput tourism village to carry out innovative promotions. It is hoped that digital media and promotional strategies prepared by the village can bring in tourists visiting the Keciput tourist village.